Science in the Trap of Fraud and Corruption - Luby, Stefan; Lubyova, Martina; Roth, Ladislav E. (Communications - Scientific letters of the University of Zilina, 2017)
The expression pathological science was introduced by I. Langmuir already in 1953. Since that time the investments into science and competition have been increasing and, consequently, the ground for scientific misconduct continues to expand. In this paper we discuss the scientific fraud in its multiple forms, such as falsification and fabrication of data, plagiarism, trading with papers and co-authorships, defrauding of funds, incorrect grant practices, etc. We identify the driving forces of misconduct as career pressure, anticipation of results, and working in the field where experiments are not precisely reproducible. The most visible fraud examples with their statistical distribution among countries and branches of science are provided. While serious cases of misconduct appear in countries with top research excellence in the process of seeking positions, awards and prizes, in the developing world the typical forms include self-plagiarism, conflict of interests in grant policy, bribery, and corruption. Finally, we elaborate on the policies supporting the research integrity.